Mycotoxins: A comprehensive review of its global trends in major cereals, advancements in chromatographic detections and future prospectives - Waqas Niaz; Shahzad Z. Iqbal; Khurshid Ahmad; Abdul Majid; Waqas Haider; Xianguo Li (Food Chemistry: X)
Mycotoxins in commonly consumed cereals pose a significant global threat to human health and economic stability. This review examines the occurrence of key mycotoxins, specifically aflatoxins (AFTs), ochratoxin A (OTA), zearalenone (ZEN), deoxynivalenol (DON), and fumonisins (FUMs) in the most widely consumed cereals: corn, wheat, and rice. The results indicate substantial regional variations, with the highest contamination levels occurring in Africa (36.59 %), Asia (33.06 %), Europe (29.06 %), and the Americas (19.20 %). Among the mycotoxins, DON exhibited the highest average contamination rate across all regions, at 49.6 %. In Africa, AFTs (63.19 %) and fumonisins (60.17 %) were particularly prevalent. Significant contamination levels of DON (55.25 %) and OTA (47.24 %) were noted in Asia. Recent advancements in liquid chromatography-tandem mass spectrometry have enhanced the sensitivity and efficiency of detection methods. This review aligns with the overarching objective of safeguarding human health from the increasing risk of mycotoxins and ensuring a sustainable food and feed supply chain.